ĐÁNH GIÁ MỨC ĐỘ PHÁT THẢI CỦA CÁC CHẤT POLYCLODIBENZO-P-DIOXIN VÀ POLYCLODIBENZOFURAN PHÁT SINH KHÔNG CHỦ ĐỊNH TỪ LÒ ĐỐT RÁC THẢI SINH HOẠT VÀ RÁC THẢI CÔNG NGHIỆP Ở VIỆT NAM - Nguyễn, Thanh Tuấn; Nguyễn, Đức Thắng; Bùi, Duy Linh; Vũ, Trung Hiếu; Nguyễn, Thị Thu Lý; Nguyễn, Thị Thu (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF THE EMISSION LEVELS OF POLYCLODIBENZO-P-DIOXIN AND POLYCLODIBENZOFURAN GENERATED UNINTENTIONALLY FROM DOMESTIC AND INDUSTRIAL WASTE INCINERATION IN VIETNAMPolychlorinated dibenzo-p-dioxins (PCDD) and polychlorinated dibenzofurans (PCDF) are the most toxic substances among the group of unintentional persistent organic pollutants (U - POP) generated from many sources, in which domestic and industrial waste incinerators are the highest emission risk. Assessment of pollution potential and dioxin/furan emissions from incinerators in developing countries, including Vietnam, is still limited; especially in-depth studies on the content and characteristics of PCDD/PCDF emitted into the atmosphere. Therefore, the research team evaluated the emission potential and characteristics of 07 PCDD and 10 PCDF, those are considered to be the most toxic isomers and congeners, from stack gas samples collected from incinerators at 33 facilities in 11 provinces in Vietnam. The total concentration of PCDD/PCDF in the industrial incinerators’ emission ranged from 37.3 to 3348.6 pg TEQs/m3 and domestic waste incinerators had lower total concentrations and fluctuated within about 37.3-1323.8 pg TEQs/m3.The characteristic of incinerator emissions is that the proportion of 2,3,7,8-TCDD accounts for 2.9 to 9.04%. The highest contributing concentrations were congeners 1,2,3,7,8-PeCDD, with its contributing percentage from 22.95-32.42%. The second largest contributor is congeners 2,3,4,7,8- PeCDF, accounting for 20.94-21.50% of the total toxic congeners of PCDD/PCDF in both types of incinerators. However, in terms of toxic equivalency (TEQ), the concentration of industrial waste incinerators is much higher than that of domestic waste incinerators. The results of stack gas samples showed that the PCDD/PCDF content for domestic waste incinerators has 5/17 establishments that exceeded the permissible standard threshold: 0.6 ng/Nm3, according to QCVN 61-MT:2016/BTNMT. Industrial waste incinerators have 5/16 establishments that exceeded the permissible standard threshold: 0.6ng/Nm3 for furnaces with a capacity of 300kg/hour according to QCVN 30:2012/BTNMT.